A review of African praying mantises (Dictyoptera: Mantodea) incorporating molecular and morphological data - Roestof, Bruce (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Praying mantises (Dictyoptera: Mantodea) are an iconic group of predatory insects, comprising around 2500 species globally, that occur in all zoogeographic regions except the poles. Their presence in the social psyche of many cultures has existed for millennia, but until the past decade, Mantodea has received little attention from the scientific community as the constituent species are of little economic or medical importance. Africa is rich in praying mantis diversity, accounting for approximately 45% of all described species, yet it remains largely under-sampled compared to the New World and Asian regions. Recent exploration of Gabon and Central African Republic have proved fruitful, with new species descriptions being major highlights. A recent re-cataloguing of southern African praying mantises has proved useful as specimen identifications were checked, new distributions were recorded, and most importantly, it was revealed that museum collections have significantly more diversity than previously recorded. A meta-analysis of African praying mantises was conducted; we present a species checklist to the countries of Africa, including Madagascar and surrounding islands. Currently, 17 families, 182 genera, and 1104 species occur in Africa.Historically, the classification of praying mantises was based solely on morphological features, and the novelty of the field at the time made it unclear which characteristics were of taxonomic importance. The onset of molecular systematics brought attention to incongruences between morphological and molecular phylogenies, believed to be attributed to convergent evolution masking the underlying evolutionary processes that occurred. Significant progress has been made in the past two decades regarding Mantodean classification and most described genera have their phylogenetic position. With the addition of more African taxa, we present mantodean phylogenies for molecular and morphological data. Molecular phylogenies were estimated through Bayesian Inference and Maximum Likelihood analyses using two nuclear (28S and H3) and two mitochondrial markers (16S and COI) for 210 individuals that represented 24 of the 29 families globally. Morphological phylogenies were estimated through Maximum Likelihood analyses of a morphological data matrix comprising 149 characters for 248 individuals that represent 24 families. The same data matrix was used to produce a key to all African mantodean families, accompanied by their descriptions.
Keywords: Biogeography; Mantodea -- Morphology; Mantodea -- Geographical distribution; Mantodea -- Classification; Sampling bias; Systematics